PENGARUH VARIASI KONSENTRASI SETIL ALKOHOL SEBAGAI EMULSIFYING AGENT PADA SEDIAAN LOTION EKSTRAK LIDAH BUAYA (Aloe vera (L.) Burm. f) - Nurmalasari, Dewi Riskha; Mardani, Alya Eka Dhyra; Eryani, Mikhania Christiningtyas (MEDFARM: Jurnal Farmasi dan Kesehatan, 2023)
Lotion is a liquid emulsion consisting of an aqueous phase and an oil phase that is stabilized by an emulsifying agent and contains one or more active ingredients. The use of cetyl alcohol as an emulsifying agent was selected because of its properties as a softener, emulsifier, and absorbing water. Cetyl alcohol can increase the stability of the consistency and improve the texture. This study aims to determine the effect of concentration variations in cetyl alcohol on the physical properties of aloe vera extract lotion. The research design used in this study is a pre-experimental preparation formula lotion that was divided into 3 sample groups with different concentrations of cetyl alcohol, namely (2%), (3%), and (4%). Then the sample will be tested for physical properties including organoleptic tests (color, texture, flavor), pH test, spreadability test, and viscosity test, homogeneity test. The research results showed that variations in cetyl alcohol concentrations affected the physical properties of the preparations organoleptic texture, and viscosity. Lotion preparations do not affect organoleptic color, flavor, pH, and homogeneity. Formulation with concentration variation of 3% cetyl alcohol had good physical properties and met the criteria including organoleptic testing with a milky white color, slightly viscous texture, strong jasmine flower flavor, pH value of 7.16 ± 0.34, spreadability value 6.99cm ± 0.18, viscosity value 31.6 dPas ± 2.88, and homogeneous. Keywords: lotion, cetyl alcohol, Aloe vera